Concordance and Clinical Outcomes Improvement Following Oral Hygiene Motivation: A Systematic Review and Report of the Workshop of the Italian Societies of Dental Hygiene - Antonia Abbinante; Anna Antonacci; Michela Antonioni; Andrea Butera; Matteo Castaldi; Silvia Cotellessa; Caterina Di Marco; Martina Gangale; Rossana Izzetti; Maurizio Luperini; Carolina Maiorani; Gianna Maria Nardi; et al. (International Journal of Dentistry)
Conclusion: Motivational interventions are effective in enhancing oral hygiene practices and improving periodontal clinical indices. Tailored motivational approaches can serve as valuable tools in promoting oral health behaviours among individuals, potentially reducing the risk of periodontal diseases. Further research is warranted to explore the long-term sustainability and scalability of motivational interventions in diverse populations and settings.